Analysis of Transient Response for Coupled Tank System via Conventional and Particle Swarm Optimization (PSO) Techniques - Jaafar, Hazriq Izzuan; Syed Hussien, Sharifah Yuslinda; Selamat, Nur Asmiza; Mohd Nasir, Mohamad Na'im; Jali, Mohd Hafiz (2014)
This paper investigates the implementation of conventional and Particle Swarm Optimization (PSO) techniques to obtain optimal parameters of controller. In this research, the transient responses of the Coupled Tank System (CTS) are analyzed with the various conventional and metaheuristic techniques which are Trial and Error, Auto-Tuning, Ziegler-Nichols (ZN), Cohen-Coon (CC), standard PSO and Priority-based Fitness PSO (PFPSO) to tune the PID controller parameters. The purpose of this research is to maintain the liquid at the specific or required height in the tank. Simulation is conducted within Matlab environment to verify the performance of the system in terms of Settling Time (Ts), Steady State Error (SSE) and Overshoot (OS). It has been demonstrated that implementation of meta-heuristic techniques are potential approach to control the desired liquid level and improve the system performances.